Pengaruh Ice Breaking Terhadap Pengelolaan Emosi Dalam Keterampilan Berbicara Siswa Sekolah Dasar Kelas III SDN 5 Suwawa Menurut Vygotsky - Dama, Yunus; Muhammad, Mulyas; Ali, Yanti; Adawiyah, Zahra Nur; Molamahu, Siti Naila; Patta, Nadia; Singgima, Kamelia Z.; Daming, Zaskia; Bahe, Elsawati (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This study aims to examine the impact of ice breaking activities on emotional control in elementary school students' speaking ability. According to Vygotsky's theory, children's learning process will be more successful if it is in the zone of proximal development and supported by pleasant social interactions. Ice breaking is used as an initial step in learning to create a positive and comfortable atmosphere. The methodology applied is direct observation and practice (turlap) on grade III students SDN 5 Suwawa. The findings show that students become more confident in speaking, can overcome nervousness, and are more active in expressing opinions after participating in ice breaking activities.